Penerapan Model Pengajaran Kolaborasi untuk Meningkatkan Prestasi Belajar Bahasa Inggris pada Materi Introduction Siswa Kelas VII A SMP Negeri 4 Taliwang Tahun Pelajaran 2019/2020 - Juberni (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2020)
This study aims to determine: (a) Improvement of English learning achievement after the implementation of the collaborative teaching model. (b) The effect of motivation to learn English after applying the collaborative teaching model. This research uses action research as much as two cycles. Each cycle consists of four stages: design, activity and observation, reflection, and revision. The target of this research is VII A grade students of SMP Negeri 4 Taliwang. The data obtained in the form of formative test results, observation sheets of teaching, and learning activities. The results of the analyst found that student achievement has increased from cycle I to cycle II namely, cycle I (58.33%) and cycle II (83.33%). The conclusion of this research is the collaborative teaching model can positively influence the achievement, interest, attention, and participation, learning motivation of Grade VII A students of SMP Negeri 4 Taliwang, and this learning model can be used as alternative learning of English.